Perbedaan Kualitas Lahan Apel Sistem Pertanian Intensif dengan Sistem Pertanian Ramah Lingkungan (Studi Kasus Di Kelompok Tani Makmur Abadi Desa Tulungrejo Kecamatan Bumiaji Kota Batu) - Indahwati, Retno; Hendrarto, Ign Budi; Izzati, Munifatul (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
The aim of this research to analyze the difference of apple farm quality the influence of intensification of agriculture system with environmentally-friendly of agriculture system. A descriptive field research was conducted in June until August 2012. The soil samples were taken in each location by using disturb sample method. The Arthropods sample were taken every five days for five time by using pitfall trap method with five transek in each location.The research applied a qualitative and quantitative-descriptive. The farm quality were comparison soil quality analyze and compositions of ground Arthropods. The composition of ground Arthropods were analyzed using Important Value Index and the diversities were analyzed by using Shannon Wiener Index. The result showed that farm quality with environmentally-friendly of agriculture system was better than intensification of agriculture system. The ground Arthropods collected at 150 pitfall trap in environmentally-friendly of agriculture system were 15.079 individual while those in intensification of agriculture system were 9.461 individual. Based on Important Value Index (40,83-64,31), Collembolla ordo Entomobryidae family dominated in each location. Based on Shannon Wiener Index that diversity of ground Arthropods in intensification of agriculture system (H’= 1,58-2,04) was greater than environmentally-friendly of agriculture system (H’= 1,56- 1,99), but both of them at medium criteria. Keywords : farm quality, agriculture system, Arthropods composition